The changing role of the supervisor - Griffith, Jerry1 Dillon, Lawrence B. (Schaumburg, Ill. : Dewar International, 1992)
Topics discussed in this video are self managing work teams, empowering employees, building trust, managing change, building a team, giving employees increasing responsibility and the new role of the supervisor
Keywords: Supervision of employees; Supervisors